2018
DOI: 10.3346/jkms.2018.33.e112
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Tolvaptan in Korean Patients with Hyponatremia Caused by the Syndrome of Inappropriate Antidiuretic Hormone

Abstract: BackgroundThe aim of this multicenter study was to evaluate the safety and efficacy of tolvaptan (TLV) in Korean patients with the syndrome of inappropriate secretion of antidiuretic hormone (SIADH).MethodsOf 51 enrolled patients with SIADH, 39 patients (16 female patients, aged 70.8 ± 11.3 years) were included in an intention to treat analysis. All patients received 15 mg/day as the initial dose, and the dose was then increased up to 60 mg/day (as needed) until day 4.ResultsSerum sodium increased significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…This increase in serum sodium concentration was observed immediately after the start of tolvaptan administration and continued throughout the treatment period; a high proportion of patients achieved normalized serum sodium concentrations. Moreover, the efficacy and safety observed in Japanese patients with SIADH in this study were similar to other results in similar populations in the USA, Canada and European countries (subgroup analysis of SALT studies) [7], the UK [9], China [10], and Korea [11].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This increase in serum sodium concentration was observed immediately after the start of tolvaptan administration and continued throughout the treatment period; a high proportion of patients achieved normalized serum sodium concentrations. Moreover, the efficacy and safety observed in Japanese patients with SIADH in this study were similar to other results in similar populations in the USA, Canada and European countries (subgroup analysis of SALT studies) [7], the UK [9], China [10], and Korea [11].…”
Section: Discussionsupporting
confidence: 90%
“…The starting dose of tolvaptan for the SIADH patients in previous clinical trials was 15 mg [7,[10][11][12]], but 7.5 mg in this study. Previously, Italian researchers have investigated the efficacy and safety of two different doses of tolvaptan (7.5 and 15 mg) in patients with hypervolemic or euvolemic hyponatremia [13].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The magnitude of the increase from baseline in serum sodium at week 1 was For the calculation of the number of events per 100 patient-years in a preferred term all episodes of an AE are counted # number of events, AE adverse event, TEAE treatment-emergent adverse event a TEAEs were AEs with onset on or after the day of first administration of tolvaptan b As rated by the physician c An AE was serious if it met any of the following criteria: resulted in death; was life-threatening (i.e., the patient was at immediate risk of death in the opinion of the physician); required in-patient hospitalization or prolonged existing hospitalization; resulted in persistent or significant disability/incapacity; was a congenital anomaly/birth defect; was a medically significant event (i.e., jeopardized the patient and required medical or surgical intervention to prevent one of the other outcomes listed) d Adverse reactions were AEs that were considered possibly or probably related to tolvaptan by the physician; AEs with missing or unknown relationship were also considered as adverse reactions e Coded by Medical Dictionary for Regulatory Activities Version 16.1 f Data were calculated using the revised criteria for an episode of rapid correction of hyponatremia. The number of events and number of events per 100 patient-years were estimated for this report based on an ad hoc analysis of patient serum sodium values, in which any changes in serum sodium levels indicative of rapid correction of hyponatremia occurring within a 48-h period were considered to be a single episode comparable to improvements (10-14 mmol/l) seen in tolvaptan studies conducted in real-word settings among populations with varying baseline sodium levels and durations of follow-up [25][26][27]. The percentage of patients in the present study with C 1 hyponatremia symptom decreased from baseline (48.4%) to the treatment period (18.3%), suggesting that improvement in sodium level was associated with improvement in hyponatremic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a prospective case series revealed that SCLC patients with SIADH responded well to 15 mg of tolvaptan per day, and no serious adverse events or neuropsychiatric deficits were observed (17). However, three studies have reported that a 15 mg dose of tolvaptan can overcorrect plasma sodium (18)(19)(20), and instead recommended an initial tolvaptan dose of 7.5 mg for patients with SIADH. Additionally, pharmacodynamic studies performed by tolvaptan manufacturers have shown that 3.75 mg can increase both urine output and plasma sodium levels (21).…”
Section: Introductionmentioning
confidence: 99%